“Flexing” and the Luxury Lifestyle: A Critique of the “False Solidarity” of Female Officials and Public Figures in Contemporary Indonesian Media - Udasmoro, Wening; Marai, Leo (The Indonesian Journal of Socio-Legal Studies, 2025)
This study aims to explore the practice of “flexing” and the luxury lifestyle as represented in the media both through the self-representation of female public figures on their social media accounts and through coverage by mainstream outlets. These figures include actresses, entertainers, and other widely recognized social personalities. The research is urgent given that the public display of wealth and opulence disseminated through the media generates a domino effect within society, particularly in shaping consumption patterns and fueling an increasingly pervasive culture of consumerism in Indonesia. The proliferation of consumerist culture both reflects and exacerbates social inequality in Indonesia, where poverty remains a fundamental challenge. A gendered perspective, especially feminist scholarship focusing on the concept of “false solidarity” is employed as the analytical lens in this research. Here, false solidarity refers to performative gestures of empathy that reinforce inequality, mock economically disadvantaged women, and normalize such practices through state institutional complicity. The method used is Critical Discourse Analysis (CDA), which examines social practices that contain elements of inequality among members of different social groups, as conveyed through the linguistic discourses circulating on social media.